2006
DOI: 10.2140/jomms.2006.1.865
|View full text |Cite
|
Sign up to set email alerts
|

The effect of contact conditions and material properties on elastic-plastic spherical contact

Abstract: The elastic-plastic contact between a sphere and rigid flat is analyzed under perfect slip and full stick conditions for a wide range of the sphere mechanical properties. The analysis provides comparison of the contact load, contact area and distribution of the contact pressure for these two contact conditions. It is found that the contact conditions and mechanical properties have little effect on the global contact parameters. However, the evolution of the plastic zone with increasing interference is substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 20 publications
7
68
0
Order By: Relevance
“…To enhance convergence, as outlined by Brizmer et al [21], the material of the sinusoidal surface was assumed elasto-plastic bi-linear isotropic hardening with a yield stress, S y , of 1 GPa and a tangent modulus, E T , 2% of the Young's modulus E. This isotropic hardening significantly improves the convergence without causing a significant change in the results.…”
Section: Elasto-plastic Fem Resultsmentioning
confidence: 99%
“…To enhance convergence, as outlined by Brizmer et al [21], the material of the sinusoidal surface was assumed elasto-plastic bi-linear isotropic hardening with a yield stress, S y , of 1 GPa and a tangent modulus, E T , 2% of the Young's modulus E. This isotropic hardening significantly improves the convergence without causing a significant change in the results.…”
Section: Elasto-plastic Fem Resultsmentioning
confidence: 99%
“…As was stated in Ref. [23], 2% isotropic hardening is the upper limit of many practical materials; it improves convergence, compared to an elastic perfectly plastic material model, with a small effect on the results (of less than 2.5%).…”
Section: Coated Sphere Under the Slip Contact Condition [25 34]mentioning
confidence: 70%
“…At higher values of Poisson's ratio, the tangential stresses under the stick contact condition are lower and the critical values for stick and for slip become comparable. Brizmer et al [23] extended the study in Ref. [22] into the elastic-plastic regime.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Brizmer et al [31] first analyzed the effect of full stick condition on the elasticity terminus of a spherical contact using finite element software ANSYS. Brizmer et al [32] extended their study for the loading of an elastic plastic spherical contact both under full stick and perfect slip contact conditions. They found that the interfacial parameters are insensitive to the contact condition and material properties of the deformable sphere.…”
Section: Introductionmentioning
confidence: 97%